The Effect of Leadership and Motivation on Employee Performance in The Muhammadiyah Zakat and Shadaqah Institution (Lazismu) Bekasi District - Harries Madiistryatno; Fahmi Hilman (Return : Study of Management, Economic and Bussines, 2023)
The main problem in this study is how much influence leadership and work motivation have on employee performance at LAZISMU Bekasi Regency, both simul- taneously and partially. The purpose of this study was to determine and analyze leadership and work motivation and employee performance and the magnitude of the influence of leadership and work motivation on employee performance at LAZISMU Bekasi Regency, either simultaneously or partially. The method used in this study is a method with a descriptive and verification approach. The population in this study were employees at LAZISMU Bekasi Regency with a sample of 40 people. The data in this study is primary data, where the data is obtained from respondents' answers to the questionnaires that the authors distribute. The results of the data analysis that the author has done, the results show that there is an influence of leadership and work motivation on improving employee performance at LAZISMU Bekasi Regency either partially or simultaneously.